EFFECT OF PLANT GROWTH REGULATORS ON GROWTH AND ESSENTIAL OIL CONTENT IN PALMAROSA (CYMBOPOGON MARTINII) - Faiz Khan, Ahamad; Mujeeb, Farina; Farooqi, A.h. A.; Farooqui, Alvina (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Objective: The aim was to examine the responses viz., herbage yield, essential oil content and oil composition to varying levels of gibberellic acid (GA3), kinetin and indole acetic acid (IAA) in Palmarosa (Cymbopogon martinii). Methods: Essential oils were obtained by hydro-distillation using a Clevenger-type apparatus and oils composition was analyzed by gas chromatography-mass spectrometry. Nitrate reductase (NR) activity was evaluated by in-vivo assay. Protein content was evaluated by Lowry method. Chlorophyll was estimated by Arnon method. Results: Plant growth was improved by GA3 significantly, and the increase was maximum at 100 ppm concentration in plant height, leaf area, tiller number and herbage yield. Chlorophyll content, protein content, NR activity and oil content increased in the plants due to GA3 treatment compared to untreated plants, and the increase was maximum at 100 ppm concentration. Effect of IAA and kinetin was similar to GA3 but maximum effect was observed at 50 ppm concentration. Geraniol content of the essential oil of Palmarosa increased due to GA3 and kinetin treatment while percentage of geranyl acetate decreased. Conclusion: On a comparative basis, among the three promotional hormones, GA3 was most effective in stimulating growth, essential oil content, leaf area, tiller number and metabolic parameters (protein content, chlorophyll content and NR activity). Keywords: Cymbopogon martinii, Essential oils, Plant growth regulators, Oil compositon. Â 